(untitled) (SMC Journal Shadananda Multiple Campus, 2026)
Several studies worldwide in the field of language acquisition have examined the importance of using children’s literature across the primary curriculum. However, in Nepal’s public primary schools, this is a very rare practice. This study, therefore, aims to investigate the effects of story reading aloud to children and of story-based activities in a primary-level classroom, and to determine whether this approach is relevant in our local context. A review of selected literature discusses the impact of literature across the curriculum on children’s overall development. The rationale for using different reading-based activities and the specific selection of stories is presented. The methodology section describes the details of how the reading intervention was carried out, including the specific context. Data were gathered from multiple sources, including children’s writing samples and response journals written by the children, their class teacher, and me as a researcher. Findings revealed the possibilities of scaffolding children’s creative thinking, creative writing, and their learning of subject content. Children were motivated to read, and my regular conversations with them enabled me to scaffold their English learning in a very low-resourced classroom.